PENGEMBANGAN LKPD BIOLOGI BERBASIS PROBLEM BASED LEARNING TERINTEGRASI UNITY OF SCIENCES UNTUK MELATIH KEMAMPUAN LITERASI SAINS SISWA KELAS XI IPA SMA - Zahra, Anisah Dwi; Anggis, Eka Vasia; Ismail, Ismail (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
Science literacy is a vital competency that equips students to address the challenges of the 21st century. To foster science literacy, effective teaching materials that support active learning are essential. This study aimed to assess the design and feasibility of a Problem-Based Learning (PBL) integrated Biology Learning Activity Sheet (LKPD) with the Unity of Sciences framework to enhance science literacy skills among Grade XI science students. The research applied a Research and Development (R&D) approach using the 4D model, consisting of the stages: Define, Design, Develop, and Disseminate. The LKPD was developed based on PBL principles and integrated with the Unity of Sciences framework, utilizing the Canva application for design. Validation results showed that media validators rated the LKPD at 77% (feasible), material validators at 92% (very feasible), learning methodology validators at 96% (very feasible), Unity of Sciences integration validators at 92% (very feasible), and the science literacy validators found that 30 literacy questions were valid. Additionally, biology teachers rated the LKPD at 88% (very feasible), and student responses also indicated a rating of 88% (very feasible). Based on these findings, the PBL-based Biology LKPD integrated with Unity of Sciences to promote science literacy skills is deemed highly feasible by expert validators, biology teachers at SMA Al-Muhadjirin, and students.